MERCOSUR : history and aims. - PEREZ DEL CASTILLO, Santiago (1993)
Describes progress towards the establishment of the Common Market of the Southern Cone. Analyses the major social and labour issues now under debate : the adoption of common standards (a charter of fundamental rights, freedom of movement, social security, etc.), employment problems, conditions of work, and the prospects for collective bargaining at community level.